Social skills training for children with Asperger syndrome and high-functioning autism - White, Susan Williams (Guilford Press, 2011)
This practical, research-based guide provides a wealth of tools and strategies for implementing social skills training in school or clinical settings. Numerous case examples illustrate common social difficulties experienced by children with Asperger syndrome and high-functioning autism; the impact on peer relationships, school performance, and behavior; and how social skills training can help. Chapters delve into the nuts and bolts of teaching and reinforcing core skills in classroom, small-group, or individual contexts, emphasizing ways to tailor interventions to each individual's needs.